2004
DOI: 10.1089/1076327041348437
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Enhances Transforming Growth Factor β-Mediated Chondrocyte Differentiation of Human Mesenchymal Stem Cells

Abstract: In clinical studies and animal models, low-intensity ultrasound (US) promotes fracture repair and increases mechanical strength. US also promotes cartilage healing by increasing glycosaminoglycan synthesis of chondrocytes. As mesenchymal stem cells (MSCs) have the ability to differentiate into chondrocytes, US may promote their differentiation. Here, we evaluated the effects of US on the differentiation of MSCs toward chondrocytes and cartilage matrix formation. When human MSCs cultured in pellets were treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
87
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 36 publications
3
87
1
Order By: Relevance
“…The osteoblast density was also found to be about 10% greater in the ultrasound model from PFW1 to PFW4, which is also reported in previous experimental studies [50][51][52][53][54]. Nevertheless no safe conclusions can be drawn for this enhancement influence since this is downstream effect and has not been explicitly modeled herein.…”
Section: Discussionsupporting
confidence: 77%
“…The osteoblast density was also found to be about 10% greater in the ultrasound model from PFW1 to PFW4, which is also reported in previous experimental studies [50][51][52][53][54]. Nevertheless no safe conclusions can be drawn for this enhancement influence since this is downstream effect and has not been explicitly modeled herein.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, Ebisawa et al showed that the LIUS treatment enhanced the TGF-β-mediated aggrecan deposition in pellet culture of human MSC (10). However, no further details on LIUS effects such as the changes in the expression of collagen type II and other related proteins were suggested in their experiment.…”
mentioning
confidence: 99%
“…Among them, TGF-β is known as a critical factor for initiation of chondrogenic differentiation in vitro and in vivo (5,7). TGF-β1 was used originally in the chondrogenic differentiation of chondrocytes and MSCs (2,8), but TGF-β2 or TGF-β3 were also shown to be effective in MSCs (5,9,10). In addition to the protein factors, mechanical factors such as cyclic compressive loading and three-dimensional (3-D) culture system are also known to induce chondrogenesis of MSCs in vitro (2,3,(11)(12)(13).…”
mentioning
confidence: 99%
“…Also, LIPUS was used for 20 minutes for one day to stimulate MSCs expansion and differentiation into chondrocytes. Matrix production was enhanced; however, cell proliferation was not enhanced (Ebisawa et al, 2004). This may also be due to using LIPUS in pellet culture.…”
Section: Lipus Utilization In Cell Expansionmentioning
confidence: 90%